1979
DOI: 10.4141/cjps79-112
|View full text |Cite
|
Sign up to set email alerts
|

Partial Control of Bitter Pit in Northern Spy Apples With a Post-Harvest Dip in Calcium Chloride Solution

Abstract: Bitter pit of Northern Spy apples that were stored in air and in controlled atmosphere (CA) storage was decreased by a post-harvest dip in 4% CaCl2 solution containing 0.35% Keltrol. The calcium treatment also decreased breakdown, loss of fruit firmness, and loss of fruit acidity, and increased Ca content of apple cortex tissue. There was no fruit injury. The dip treatment increased rots in one instance, presumably from dispersal of fungal spores during the dipping process and not due to an effect of calcium. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
5
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 6 publications
2
5
0
Order By: Relevance
“…Practices that can reduce 'Honeycrisp' bitter pit development include field-applied calcium (Biggs and Peck, 2015;Peryea et al, 2007;Rosenberger et al, 2004), optimal crop load (Delong et al, 2006;Robinson and Lopez, 2012) and harvest at optimal maturity (Prange et al, 2011). After harvest, bitter pit development can be reduced by calcium dips (Reid and Padfield, 1975) as well as CA storage (Hewett, 1984;Sharples, 1982;Webster and Forsyth, 1979). A short period of CA that creates low oxygen stress established during temperature conditioning also can reduce bitter pit development (Pesis et al, 2010) as can a nonstress CA that is continued throughout cold storage (Mattheis et al, 2017).…”
mentioning
confidence: 99%
“…Practices that can reduce 'Honeycrisp' bitter pit development include field-applied calcium (Biggs and Peck, 2015;Peryea et al, 2007;Rosenberger et al, 2004), optimal crop load (Delong et al, 2006;Robinson and Lopez, 2012) and harvest at optimal maturity (Prange et al, 2011). After harvest, bitter pit development can be reduced by calcium dips (Reid and Padfield, 1975) as well as CA storage (Hewett, 1984;Sharples, 1982;Webster and Forsyth, 1979). A short period of CA that creates low oxygen stress established during temperature conditioning also can reduce bitter pit development (Pesis et al, 2010) as can a nonstress CA that is continued throughout cold storage (Mattheis et al, 2017).…”
mentioning
confidence: 99%
“…Bitter pit symptoms are often absent at harvest and develop during the postharvest period in storage (Ferguson and Watkins, 1989;McAlpine, 1912). Storage in a lowoxygen CA can reduce bitter pit development (Hewett, 1984;Sharples, 1982;Webster and Forsyth, 1979) while impacts of postharvest 1-MCP application have been mixed (Calvo and Candan, 2010;Gago et al, 2015;Mirzaee et al, 2015).…”
mentioning
confidence: 99%
“…Granny Smith apples dipped in 2% or 4% CaCl2 were less incidence significantly than untreated apples or that treated with AVG, which showed the highest bitter pit incidence (45.93, 44.43 and 43.2%). Some studies found that apple fruit dip in Ca salts resulted in bitter pit incidence reduction Wills, 1977 andWebster andForsyth, 1979). 2-Superficial scald: No significant differences appeared between all treatments of CaCl 2 and AVG, except 2% CaCl 2 treatment in Granny Smith apples which gave the lowest value (5.04%), and differed significantly with the highest value (20.8%) of the control treatment.…”
Section: Methodsmentioning
confidence: 96%